Evaluation of the survivability of CFRP honeycomb-cored panels in compression after impact tests (Fracture and Structural Integrity, 2021)
This paper is oriented to the experimental research of the mechanics of the CFRP sandwich plates, glass and carbon fiber sample panels with a large-cell honeycomb core. The method for testing polymer composite sample plates in compression after impact (CAI) tests with joint use of a testing machine and a video system for deformation field registration was tested. Analysis of the experimental data obtained highlighted the impactive sensitivity zone for the test specimens. A quantitative assessment of the load-bearing capacity of glass and carbon fiber sample panels in CAI tests with the different levels of the drop weight impact energy was performed. Photos of samples after impact have been provided.Vic-3D non-contact three-dimensional digital optical system was used to register the displacement and deformation fields on the surface of the samples. The video system was used to evaluate various damage mechanisms, including matrix cracking, delaminations, and rupture of the damaged fibers. The paper studied the evolution of non-homogeneous deformation fields on the surface of the composite samples during the post-impact compression tests and analyzed the configuration of non-homogeneous deformation fields.
Keywords: Composite materials; Testing; Compression after impact; Digital image correlation; Stress concentrators; Complex mechanical loads; Residual strength; Life prediction